Biologic Knee Reconstruction: A Surgeon's Guide - Cole, Brian; Harris, Joshua (Taylor & Francis Group, 2015)
Treatment of articular cartilage pathology in the knees of young and active patients is a challenging and controversial issue. Biologic Knee Reconstruction: A Surgeon's Guide is a how-to, step- by-step guide that addresses the evaluation and management of this unique patient population. Internationally renowned cartilage experts Dr. Brian J. Cole and Dr. Joshua D. Harris, along with their contributors, present information on normal and abnormal history and physical examination. The reader will learn proper decision-making using a patient-centered approach of treatment, increasing the likelihood of a successful outcome. In addition to radiographic assessment of articular cartilage, Biologic Knee Reconstruction discusses the use of biomarkers, defect classification, and patient-reported and surgeon-measured outcomes. Aggressive nonsurgical medical management, including medications, injections, physiotherapy, and rehabilitation, is also presented. Biologic Knee Reconstruction also discusses the management of concomitant pathologies such as malalignment, meniscal deficiency, and ligamentous instability. Selection of surgical cartilage restorative treatment options is multifactorial, requiring consideration of several patient-, knee-, and defect-specific issues. All contemporary open and arthroscopic cartilage techniques are presented in detail with high resolution figures. A unique feature of Biologic Knee Reconstruction is the presentation of several chapters discussing non-medical issues highly pertinent to the advancement and future of this field: funding of research and cost of new advanced technologies, regulation of advanced cellular, tissue, and genetic technologies, evidence-based medicine and clinical trial design and conduct, and the ethics of allograft tissues and stem cell use. Features: * Technique preference cards from the experts performing cartilage surgery * Patient education information * The most up-to-date descript